FUNCTIONAL TRAINING: THE IMPACT ON IMPROVING THE QUALITY OF LIFE IN THE ELDERLY - Dantas da Silva, Eduardo; da Silva Santos, Tatiana (Health and Society, 2023)
This work is a review of the literature which used the main databases such as SCIELO and PUBMED, bringing together 7 articles in Portuguese and English from 2013 to 2023, on the benefits of functional training for the elderly, as the Aging is a set of morphological, physiological, biochemical and psychological changes that depend on the individual’s life history and genetics. It is common to observe a reduction in the percentage of lean mass in the elderly, which may be related to a decrease in muscle strength. Functional training is effective in strengthening muscles, improving mobility and balance, ensuring the prevention of falls and, consequently, improving the quality of life for the elderly.